Implementasi Metode Tonika Solfa Dalam Pembelajaran Teori Dasar Musik Siswa Kelas VIII Di SMP Negeri 21 Medan - Sinaga, Novelia Igres; Sinaga, Theodora; Wiflihani, Wiflihani (Jurnal Pendidikan dan Penciptaan Seni, 2023)
This study aims to determine the learning of the Implementation of the Tonika Solfa Method in learning the basic theory of music, to find out the constraints that occur during the learning process and to find out the results after the implementation of the implementation of the tonica solfa method in learning the basic theory of music in eighth grade students at SMP Negeri 21 Medan. The method used in this research is descriptive qualitative method. The population in this study were all students of class VIII and the sample in this study were 23 people. This study uses data collection techniques such as observation, interviews and documentation. The results of this study found that the Implementation of the Solica Tonika Method describes how to use the tonica solfa method in reading the scales included in the song and the use of rythimsilabes using hand movements. The learning process of the Solica Tonika Method Implementation, which explains the tonica solfa method in learning the basic theory of music and the parts that are in the tonica solfa method, are explained to students of Class VIII at SMP Negeri 21 Medan